2016
DOI: 10.15193/zntj/2016/104/098
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of lactic acid bacteria of Lactobacillus genus

Abstract: AKTYWNOŚĆ PRZECIWGRZYBOWA BAKTERII FERMENTACJI MLEKOWEJ Z RODZAJU LACTOBACILLUSS t r e s z c z e n i e Jedną z metod ochrony żywności fermentowanej przed bytującymi w niej niepożądanymi mikroorganizmami jest zastosowanie bakterii mlekowych jako naturalnych biokonserwantów. Szczególnie korzystna jest obecność bakterii fermentacji mlekowej (LAB) w żywności. Oprócz spodziewanej aktywności antybakteryjnej i przeciwgrzybowej LAB cechują się korzystnym wpływem na organizm człowieka poprzez stymulowanie przewodu poka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Of particular application interest are lactobacilli, which convert carbohydrates into lactic and acetic acids (primary metabolites), as well as a range of secondary metabolites, such as carbon dioxide, ethanol, hydrogen peroxide, fatty acids, acetoin, diacetyl, cyclic dipeptides, bacteriocins, and bacteriocin-like inhibitory substances [ 3 ]. Since these metabolites exhibit only weak antifungal properties, many research teams are seeking Lactobacillus strains with a higher natural ability to inhibit fungal and yeast growth [ 4 , 9 , 14 , 15 , 26 ]. Ryu et al [ 26 ] reported that Lactobacillus plantarum HD1 synthesizes 5-oxododecanoic acid (MW 214), 3-hydroxydecanoic acid (MW 188), and 3-hydroxy-5-dodecenoic acid (MW 214), which are considered antifungal.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular application interest are lactobacilli, which convert carbohydrates into lactic and acetic acids (primary metabolites), as well as a range of secondary metabolites, such as carbon dioxide, ethanol, hydrogen peroxide, fatty acids, acetoin, diacetyl, cyclic dipeptides, bacteriocins, and bacteriocin-like inhibitory substances [ 3 ]. Since these metabolites exhibit only weak antifungal properties, many research teams are seeking Lactobacillus strains with a higher natural ability to inhibit fungal and yeast growth [ 4 , 9 , 14 , 15 , 26 ]. Ryu et al [ 26 ] reported that Lactobacillus plantarum HD1 synthesizes 5-oxododecanoic acid (MW 214), 3-hydroxydecanoic acid (MW 188), and 3-hydroxy-5-dodecenoic acid (MW 214), which are considered antifungal.…”
Section: Introductionmentioning
confidence: 99%
“…8) The antifungal activity of Lactobacillus was enhanced in the presence of xylitol and sorbitol. 9,10) Xylitol and sorbitol also enhanced the fungicidal effect of benzethonium chloride in vitro C. albicans biofilm. 11) A decrease in the number of yeast in human stool was observed after a single 30 g oral dose of xylitol.…”
Section: Introductionmentioning
confidence: 92%
“…In the presence of xylitol and sorbitol, antifungal activities of Lactobacillus were enhanced and these effects were suggested to be due to the synthesis of specific metabolites and/or peptides with antifungal properties. 9,10) Similarly, the growth and invasion of C. albicans in the gastrointestinal tract were influenced by the types of carbohydrate supplementation. Xylitol intake inhibited the growth of C. albicans in the gastrointestinal tract compared to sucrose intake.…”
Section: Candidacidal Activity Of Xylitol and Sorbitol At A High Concmentioning
confidence: 99%
“…Kefir is defined as a beverage with antibacterial, antifungal [9][10][11], and antioxidant properties [12][13][14]. There are also data indicating the anticancer properties of kefir [13,15,16]. Literature data showed that kefir grain microflora is a complex of microorganisms characterized by the ability to release and produce compounds with bioactive properties from milk and its fraction (whey) [6,9,16].…”
Section: Introductionmentioning
confidence: 99%
“…Factors affecting the growth of microorganisms include temperature, the concentration of hydrogen ions, redox potential, water activity, and hydrostatic pressure [15].…”
Section: Introductionmentioning
confidence: 99%